The Influence of Motivation and Work Discipline on Employee Performance at the Gowa Regency DPRD Secretariat - Raskin Raskin; Muhammad Yusuf; Andi Arif Wangsa Adiningrat (Pustaka Digital Indonesia, 2026)
The urgency of this research is to analyze the role of motivation and work discipline in improving employee performance at the Gowa Regency DPRD Secretariat. Employee performance is a crucial factor in determining the effectiveness of public sector organizations, as it directly influences the achievement of organizational goals and the quality of public services. Therefore, understanding the factors that contribute to employee performance, particularly work motivation and work discipline, is essential for improving organizational outcomes. This study aims to analyze the effect of work motivation and work discipline on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Gowa Regency. A quantitative approach with descriptive and associative methods was employed. The study involved a saturated sample of 32 employees, with data collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 26. The findings indicate that work motivation has a positive and significant effect on employee performance, suggesting that higher motivation levels lead to improved work outcomes in terms of quality, responsibility, and productivity. In contrast, work discipline does not show a significant partial effect on performance, indicating that compliance with rules alone is insufficient to enhance performance without strong internal drive. However, simultaneous testing reveals that motivation and work discipline together have a positive and significant effect on employee performance, with a coefficient of determination of 59.2%. This implies that both variables collectively explain a substantial proportion of performance variation, while the remaining 40.8% is influenced by other factors not examined in this study. The findings emphasize that organizations should strengthen employee motivation and implement effective work discipline through balanced human resource strategies, as both factors jointly improve employee performance, with motivation serving as the dominant influence.